2018
DOI: 10.1021/acsomega.7b01533
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Tyrosylprotein Sulfotransferases for In Vitro One-Pot Enzymatic Synthesis of Sulfated Proteins/Peptides

Abstract: Protein tyrosine sulfation (PTS), catalyzed by membrane-anchored tyrosylprotein sulfotransferase (TPST), is one of the most common post-translational modifications of secretory and transmembrane proteins. PTS, a key modulator of extracellular protein–protein interactions, accounts for various important biological activities, namely, virus entry, inflammation, coagulation, and sterility. The preparation and characterization of TPST is fundamental for understanding the synthesis of tyrosine-sulfated proteins and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The results revealed that in situ PTS could be achieved through coupled enzyme treatment, and this was used as supporting data for the following experiment in which in situ PTS was catalyzed on the pSNWFET surface. method that can be used to determine the sulfated protein [28]. The PTS reaction monitored through ELISA was similar to that described in Scheme 2 for PTS on the pSNWFET, with minor modifications.…”
Section: Identification Of In Situ Pts With Elisamentioning
confidence: 99%
“…The results revealed that in situ PTS could be achieved through coupled enzyme treatment, and this was used as supporting data for the following experiment in which in situ PTS was catalyzed on the pSNWFET surface. method that can be used to determine the sulfated protein [28]. The PTS reaction monitored through ELISA was similar to that described in Scheme 2 for PTS on the pSNWFET, with minor modifications.…”
Section: Identification Of In Situ Pts With Elisamentioning
confidence: 99%
“…The sulfate group is a ubiquitous post‐translational modification that accounts for approximately 1 % of all known epigenetic markers, and plays a vital role in a variety of biological processes, including protein–protein and oligosaccharide interactions …”
Section: Methodsmentioning
confidence: 99%
“…Methods to prepare sulfated proteins have focussed on the sulfated amino acid sY, with very limited examples of sS and sT . The pre‐installation of a sulfate group onto Y is possible, using alternative protecting group methods, but with the added complication of the instability of sY to solid‐phase peptide cleavage.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations